PENGARUH KOMPOSISI PAKAN BERBEDA TERHADAP PERTUMBUHAN IKAN NILA (Oreochromis niloticus) - Nerzon Jhonaidi; zulkhasyni zulkhasyni; Andriyeni Andriyeni (University of Prof. Dr. Hazairin, SH, 2020)
Feed is one of the most important elements to support a fisheries aquaculture business activity. This study aims to examine the effect of feed composition on the growth of tilapia (Oreochromis niloticus). The studi used a completely randomized design with three treatments and five replications. The treatments that tested were P1 = Kangkung Plant 100%, P2 = Lamtoro Leaf 100%, P3 = Kangkung Plant 50% + Lamtoro Leaf 50%. To find out whether there was an influence or not on the treatment, analysis of variance was performed, while to see the effect of the best composition, a further test of Least Significant Difference (LSD) was performed at 5% and 1% levels. The parameters observed were absolute length, absolute weight, feed conversion, feed efficiency and survival. The results showed that different feed compositions did not affect absolute length and survival, but significantly affected the absolute weight of feed conversion and feed efficiency. The highest absolute length growth was the spinach plant 50% + Lamtoro leaf 50%, while for absolute weight, the best feed conversion and feed efficiency were found in lamtoro leaves with a survival rate of 92.50%.